2018
DOI: 10.1073/pnas.1711356115
|View full text |Cite
|
Sign up to set email alerts
|

Pathology after Chlamydia trachomatis infection is driven by nonprotective immune cells that are distinct from protective populations

Abstract: Infection with drives severe mucosal immunopathology; however, the immune responses that are required for mediating pathology vs. protection are not well understood. Here, we employed a mouse model to identify immune responses required for-induced upper genital tract pathology and to determine whether these responses are also required for bacterial clearance. In mice as in humans, immunopathology was characterized by extravasation of leukocytes into the upper genital tract that occluded luminal spaces in the u… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
39
0

Year Published

2019
2019
2021
2021

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 47 publications
(39 citation statements)
references
References 16 publications
0
39
0
Order By: Relevance
“…We have previously established one such transgenic mouse, denoted the NR1 mouse, in which CD4 ϩ T cells are specific for the C. trachomatis protein Cta1 (6). Following C. trachomatis infection, NR1 T cells can home to the genital tract using specific chemokine receptors (9) and host integrins (10) that are similar to those used by endogenous T cells (11)(12)(13). NR1 T cell homing to the genital tract is essential for C. trachomatis clearance, as T cells that cannot home to the genital tract are unable to clear infection (9,10).…”
mentioning
confidence: 99%
“…We have previously established one such transgenic mouse, denoted the NR1 mouse, in which CD4 ϩ T cells are specific for the C. trachomatis protein Cta1 (6). Following C. trachomatis infection, NR1 T cells can home to the genital tract using specific chemokine receptors (9) and host integrins (10) that are similar to those used by endogenous T cells (11)(12)(13). NR1 T cell homing to the genital tract is essential for C. trachomatis clearance, as T cells that cannot home to the genital tract are unable to clear infection (9,10).…”
mentioning
confidence: 99%
“…The similarity in uterine necrosis noticed in all mice groups could be due to histological and functional remodeling of the endometrium during the estrous cycle 21 , 22 . The lymphocytic inflammation contained increased numbers of CD4-positive lymphocytes, which are associated with Chalmydia l 23 26 . In this study we housed the ECD mice under normal LD conditions after infection.…”
Section: Discussionmentioning
confidence: 99%
“…Pathology from chlamydial infection is associated with host immune response to Chalmydia 20 , 23 , 27 . Cytokines and chemokines are important mediators of this immune response 28 30 .…”
Section: Discussionmentioning
confidence: 99%
“…Given that there are greater numbers of CD4 ϩ T cells in the genital tracts of mice following transcervical infection, it is likely that this enhanced population contributes significantly to higher levels of IFN-␥ in the upper genital tract. While CD4 ϩ T cells are necessary for Chlamydia clearance (5,22), antigen-nonspecific bystander CD4 ϩ T cells have been found to contribute to immunopathology in mice infected with C. trachomatis serovar D (23). Furthermore, it has been recently demonstrated that CD4 ϩ T cells can induce pathology in mice deficient in CD8 ϩ T cells, following C. muridarum infection (24).…”
Section: Discussionmentioning
confidence: 99%
“…Tissues were sent to the Rodent Histopathology Core Facility at Harvard Medical School for sectioning and hematoxylin and eosin (H&E) staining. Sections were assessed for immunopathology as described previously (23).…”
Section: Methodsmentioning
confidence: 99%